2007
DOI: 10.1086/519019
|View full text |Cite
|
Sign up to set email alerts
|

GRB 060714: No Clear Dividing Line between Prompt Emission and X‐Ray Flares

Abstract: The long gamma-ray burst GRB 060714 was observed to exhibit a series of five X-ray flares beginning $70 s after the burst trigger T 0 and continuing until $T 0 þ 200 s. The first two flares were detected by the Burst Alert Telescope (BAT) on the Swift satellite, before Swift had slewed to the burst location, while the last three flares were strongly detected by the X-Ray Telescope (XRT) but only weakly detected by the BAT. This burst provides an unusual opportunity to track a complete sequence of flares over a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 59 publications
5
42
0
Order By: Relevance
“…The lack of optical variations is consistent with previously reported observations (e.g. Burrows et al 2005;Krimm et al 2007;Butler & Kocevski 2007). The optical spectral index also unchanged during the X-ray flares in both GRB 071112C and 080506.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of optical variations is consistent with previously reported observations (e.g. Burrows et al 2005;Krimm et al 2007;Butler & Kocevski 2007). The optical spectral index also unchanged during the X-ray flares in both GRB 071112C and 080506.…”
Section: Discussionsupporting
confidence: 92%
“…No optical-infrared flare has been reported during the X-ray flares in previous observations, while a part of those observations were too sparse to investigate the detailed behavior of optical-infrared afterglows during the X-ray flares (Stanek et al 2007;Krimm et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The flares are relatively sharp, with ∆t/t ∼ 0.1, and are spectrally different (harder) than the underlying afterglow emission. There is considerable spectral evolution during a flare with a hardening during the rise followed by softening during the decay Krimm et al, 2007;Godet et al, 2007). The first case where these flares were seen simultaneous in the optical/NIR was GRB 071031 (Krühler et al, 2009), which showed that the peak of the emission shifts at late times from the few keV band into the UV.…”
Section: X-ray Flaresmentioning
confidence: 99%
“…Burrows et al 2005;Chincarini at al. 2007;Krimm et al 2007), and strong optical/NIR flaring contemporaneous with the GRB prompt emission may also occur (Vestrand et al 2005Blake et al 2005;Racusin et al 2008), thus making optical flares from late central engine activity an interesting prospect (Kann 2007;Malesani et al 2007). …”
Section: Discussionmentioning
confidence: 99%